Herman Melville's Billy Budd, Benito Cereno, Bartleby the scrivener, and other tales - Bloom, Harold (New York : Chelsea House, 1987)
A collection of seven critical essays on Melville's shorter works of fiction including "Billy Budd" and "The Piazza Tales."
Includes bibliographical references (p. 153-156) and index.
Young Adult
Keywords: Melville, Herman, -- 1819-1891 -- Criticism, interpretation, etc; American literature -- History and criticism